Analysis of Creative Thinking Skills of Senior High School Phase E Students through Mind Maps on The Subject of The Nature of Chemistry - Mahdiah, Munifa; Faizah Qurrata Aini (Journal of Tropical Chemistry Research and Education, 2025)
The main problem in this study is that no analysis has been conducted on the level of creative thinking ability of students, especially in public high schools in the city of Padang, causing teachers to lack accurate data on the effectiveness of the learning efforts that have been implemented. This study aims to analyze the level of creative thinking ability of students in the subject of the nature of chemistry, which is examined in four aspects, namely fluency, flexibility, originality, and elaboration. This study uses a descriptive method with a quantitative approach involving 40 students in phase E of SMAN Padang. Primary data was obtained from mind maps created by students and then analyzed using instruments. The results of the study were reviewed from each aspect, with the highest achievement obtained in the aspect of fluency with a percentage of 79.37%. Furthermore, the flexibility aspect obtained a percentage of 75.00%, which indicates the students' ability to categorize concepts appropriately and diversely. The originality aspect was recorded with an achievement of 60.55%. Conversely, elaboration was the aspect with the lowest achievement, at only 26.66%, indicating that students still had difficulty elaborating ideas in detail and connecting concepts between hierarchies or within a single hierarchy. It can be concluded that the majority of students were in the less creative category, namely 29 students. Meanwhile, there were 10 students in the creative category, 1 student in the not creative category, and no students in the very creative category. Keywords: creative thinking; Essence of Chemistry; Mind Maps; Students in Phase E